Improved fault-ride-through capability of grid connected wind turbine driven DFIG - Le, Hai; Islam, Syed (Curtin University of Technoklogy, 2007)
This paper discusses dynamic model of DFIG wind generator and improvement of controllers for better interaction between wind farm and power system during transient grid fault events. The improvements include Controller Implementation of blade pitch angle, frequency stabilizer, drive train stabilizer and STATCOM operation of the grid side converter.